Crooked river [compact disc, unabridged] - Preston, Douglas J; Child, Lincoln (Preston, Douglas J. Pendergast novel., 2020)
Dozens of identical blue shoes are found in the ocean off the coast of Florida, all with a severed human foot inside. Pendergast reluctantly arrives on Captiva Island and is quickly drawn into the mystery.